Group Counseling through Cognitive Behavioral Therapy with Cognitive Restructuring Technique for Self-Esteem Enhancement of Bullying Victims - Malya Milawati; Awalya Awalya; Siti Nuzulia (Universitas Negeri Semarang, 2025)
Students with high self-esteem possess a positive self-concept and a confidence to navigate psychological and social challenges as part of their developmental process. However, victims of bullying tend to exhibit low self-esteem, characterized by feelings of worthlessness, pervasive self-doubt, and the emergence of maladaptive negative thought patterns. Consequently, this study aimed to enhance the self-esteem of bullying victims through a group counseling intervention utilizing cognitive behavioral therapy (CBT) with a focus on cognitive restructuring technique. The research employed a quasi-experimental one-group pre-test-post-test design, involving two phases of measurement (pre and post-test). Six students identified as having low self-esteem were selected as participants. The analysis revealed a notable improvement in self-esteem based on the different test results before and after the intervention. Specifically, the Wilcoxon signed-rank test demonstrated a significant increase from pre-test to post-test scores. Overall, group counseling utilizing cognitive restructuring proved effective in assisting bullying victims to foster more positive self-perceptions that elevate their self-esteem. These findings provide a theoretical and practical basis for school counselors to implement cognitive restructuring as a primary intervention for supporting students who have experienced bullying.